2012
DOI: 10.1103/physrevb.85.024533
|View full text |Cite
|
Sign up to set email alerts
|

Probing phase coherence in solid helium using torsional oscillators of different path lengths

Abstract: Long range phase coherence is a critical signature of macroscopic quantum phenomena. To date, non-classical rotational inertia (NCRI) of solid helium has been reported only in samples with physical dimension of at most five centimeters. We have investigated solid helium in longer path length torsional oscillators. Samples of length ranging from 6 to 100 cm were grown inside toroids and in self-connected long capillaries. NCRI of 4 × 10 −5 and 3 × 10 −5 were found in cells with path length of 6 and 9 cm. In cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
4
14
0
Order By: Relevance
“…For our open cylindrical cell we get a reduction in the sensitivity of about a factor of two compared with the case of a single-mode oscillator. Even with that reduction, our sensitivity to changes in the moment of inertia of the helium is around Δp F =p = 0.01, comparable to the numbers reported by the Chan group for their high-sensitivity long-path-length experiments (35).…”
Section: Significancesupporting
confidence: 84%
“…For our open cylindrical cell we get a reduction in the sensitivity of about a factor of two compared with the case of a single-mode oscillator. Even with that reduction, our sensitivity to changes in the moment of inertia of the helium is around Δp F =p = 0.01, comparable to the numbers reported by the Chan group for their high-sensitivity long-path-length experiments (35).…”
Section: Significancesupporting
confidence: 84%
“…Another important development in the investigation of magnetism in quasicrystals was the discovery of AFM order in the R Cd 6 cubic approximants, first indicated by bulk magnetization measurements [47, 49, 50] and established to be long-range AFM order by x-ray resonant magnetic scattering (XRMS) measurements at the Tb x-ray absorption edge of a single crystal [48]. Figure 11 shows the magnetic susceptibility of which exhibits anomalies at = 24 K, = 19 K and = 2.4 K [47].…”
Section: Binary Magnetic Icosahedral Quasicrystals and Approximants Imentioning
confidence: 99%
“…The XRMS measurements on [48] and [51] clearly demonstrated that long-range AFM order is established in these approximants below 24 K and 8.5 K, respectively. Shown in figure 12 are scans through the charge peak and magnetic peak positions showing that sharp Bragg peaks are observed for the magnetic scattering from with a magnetic correlation length greater than 500 Å.…”
Section: Binary Magnetic Icosahedral Quasicrystals and Approximants Imentioning
confidence: 99%
“…In some TOs, solid helium contributes significantly to the mechanical coupling of the different parts of the torsion cell. The coupling is strengthened when the solid helium sample is stiffened at low temperature resulting in a lower resonant period [4,17]. The torsion rod is usually attached at the center of one end of the (cylindrical) torsion cell.…”
mentioning
confidence: 99%